Pelatihan Strategi Pengembangan Perpustakaan Sekolah Tingkatan Menengah Se-Kecamatan Tlanakan - Agus Subaidi; Moh Zayyadi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
The library is part of school facilities that must be managed properly. But in reality, in the field there are still many school libraries that are still not good in the management system such as reading room arrangement that is not comfortable, books that are not labeled so that it is difficult for readers to look for it, it is difficult to know the availability of books (administrative services using manuals) and there are still many librarians who Not yet qualified in their fields, there are even librarians who are not purely library subjects, so there is a need for training and education for librarians and providers in the school library. We see the need for library development in several schools in Tlanakan sub-district. Because it can increase interest in visiting and reading students. So that the target in achieving is the increase of librarian's knowledge and ability in managing the school library properly so that the library becomes a maximum means of supporting student learning. The findings of this activity are the participants responded well. They get a lot of previously unknown knowledge about library management and are motivated to develop libraries in their schools and plan to follow other trainings that support their knowledge in managing the library.